MANGKIKI’: Kajian Misi Transformasi terhadap Budaya Mangkiki’ di Kalangan Penganut Aluk Toyolo di Mamasa - D, Yuliana; Bamba, Arruan; Maviana, Anggriel (Melo: Jurnal Studi Agama-agama, 2024)
Abstract: This study delves into the transformative mission of the church in the Aluk Toyolo culture of Mamasa about ritual of "Mangkiki'." As the church holds the responsibility to perpetuate God's mission, cultural engagement becomes paramount. The cross-cultural communication of the Gospel, especially in contexts like Aluk Toyolo, necessitates an approach contextualizes the local culture for effective transformation. Aluk Toyolo, a traditional belief system deeply rooted in Mamasa's history, poses unique challenges for Gospel integration. The ritual of "Mangkiki'" involves offering portions of slaughtered animals to earthly and celestial deities, seeking blessings, health, and prosperity. Despite being predominantly Christian, Mamasa society continues to observe Aluk Toyolo traditions, reflecting the significance of cultural heritage. Unlike previous perspectives that viewed culture through the lens of church determination, this study proposes a dialogical approach. The church, rather than dictating cultural acceptability, engages in a dialogue with the culture to foster transformation within its unique context. The objective is not to eliminate cultural practices but to preserve them as integral components of identity within the society community. Utilizing a qualitative methodology with descriptive analysis, this research employs literature studies, interviews, and observations to unravel the dynamics of "Mangkiki'" and its potential for Gospel-driven cultural transformation. By understanding and appreciating the cultural nuances, the church can facilitate a dialogue that promotes and fosters transformation based on Gospel values. A change in meaning and outlook that is in line with tehe values of Gospel toard culture is the mission transformation. Mangkiki’ isi a cultural ritual which is interpreted based on God’s Word that the sourch of blessing is not from the result of Mangkiki’ but comes from God. Abstrak: Penelitian ini membahas misi transformasi gereja dalam budaya Aluk Toyolo di Mamasa tentang ritual Mangkiki'. Gereja memiliki tanggung jawab untuk melanjutkan misi Tuhan. Komunikasi lintas budaya tentang Injil, terutama dalam konteks seperti Aluk Toyolo, memerlukan pendekatan mengkontekstualisasikan Injil terhadap budaya lokal untuk transformasi yang efektif. Aluk Toyolo, sebagai sistem kepercayaan tradisional yang berakar dalam sejarah Mamasa, menimbulkan tantangan unik bagi integrasi Injil. Ritual Mangkiki melibatkan persembahan bagian-bagian hewan yang disembelih kepada dewa-dewa bumi dan langit, mencari berkat, kesehatan, dan kemakmuran. Gereja hendaknya menerima budaya sebagai warisan dan terlibat dalam dialog dengan budaya untuk mendorong transformasi dalam konteksnya yang unik. Tujuannya bukan untuk menghapus praktik budaya, melainkan mempertahankannya sebagai komponen integral identitas dalam komunitas masyarakat. Penulis menggunakan metodologi kualitatif dan analisis deskriptif, penelitian ini memanfaatkan studi literatur, wawancara, dan observasi untuk mengungkap dinamika Mangkiki’ dan potensinya dalam transformasi budaya yang didorong oleh Injil. Memahami dan menghargai nuansa budaya, gereja dapat memfasilitasi dialog yang mempromosikan dan mendorong transformasi berdasarkan nilai-nilai Injil. Adanya perubahan makna dan pandangan yang sesuai dengan nilai Injil terhadap budaya itulah misi transformasi. Mangkiki’ adalah suatu ritual dari budaya yang dimaknai berdasarkan Firman Tuhan bahwa sumber berkat diperoleh bukan dari hasil Mangkiki’ melainkan bersumber dari Tuhan.